Economic and Behavioral Determinants of Financial Decision Making in Tourism through Spending Intention - Ni Komang Septia Noriska; Yohanes Wien Tineka; Agreianti Puspitasari; Vivin Sulistyowati; Muhammad Tafdhil Amanda; Brian Gregory Adhihendra (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2026)
Financial decision making in tourism is increasingly influenced by economic and behavioral factors. However, previous studies have not sufficiently explained the mediating role of spending intention in linking these factors to financial decision making. A quantitative research design was adopted for this study to evaluate the roles of economic and behavioral factors in financial decision making, where spending intention was hypothesized as a mediating variable, and survey responses collected from 100 domestic tourists provided the empirical basis for analysis using the Partial Least Squares approach to Structural Equation Modeling. The findings reveal that both economic and behavioral variables significantly influence spending intention and also exert significant direct effects on financial decision making, and spending intention is found to have a positive significant impact on financial decisions while partially mediating the associations between the predictor variables and the outcome variable. Substantial explanatory power is evidenced by the structural model, with R² statistics reaching 0.596 for the spending intention construct and 0.680 for financial decision making, which implies that financial behavior is jointly determined by economic stimuli and psychological drivers, with spending intention constituting a critical conduit for these effects. Through its integration of economic and behavioral viewpoints within a unified empirical framework, this study advances the behavioral tourism literature and offers actionable insights for destination managers and tourism businesses in devising promotional strategies that foster sustainable consumer spending.